Application of Mechanical Relations in Mathematical Modeling to Oxygenate Synthetic Wastewater through a Circular Rotary Aerator - Cornejo Tueros, Jose Vladimir (2021)
This paper expounds the issue about the evolution of the dissolved oxygen concentration in synthetic wastewater with a circular rotary by setting a mathematical model. The mathematical model is based on the Lewis and Whitman relations to transfer oxygen to water, and includes the mechanistic models proposed by Lee, to determine the global oxygen transfer coefficient and the oxygen saturation concentration in water, as a function of the fifth power temperature. For this purpose, historical data from aeration experiments with two types of discs and two levels of COD concentration were compared. The equation allows to include the effect of the variation of the temperature and atmospheric pressure. Finally, through the data obtained, it's concluded that the estimation error is not affected by the type of disc, the COD concentration of the synthetic wastewater or by the interaction of both, and is less than + - 0.086 mg / L dissolved oxygen.